Evaluation of Conventional Methods in Reducing Heavy Metal Concentrations in Industrial Waste - Nurmustaqimah; Zahrul Mufrodi; Siti Jamilatun (Indonesian Journal of Chemical Engineering, 2025)
The rapid growth of the chemical industry has increased liquid waste containing heavy metals (Cadmium, Zinc, Lead), which threaten ecosystems and human health due to persistence and biomagnification. The handling of these effluents requires specific methods according to the characteristics of the effluents. Electrochemical processes stand out in heavy metal removal efficiency, while adsorption using natural materials (fruit peels, sawdust) offers lowcost effectiveness. Ion flotation utilizes surfactants, although its efficiency depends on operational conditions. Chemical precipitation with lime is a cheap solution to reduce metal solubility, while phytoremediation relies on plants as an environmentally friendly alternative. The selection of methods is based on the type of metal, waste concentration, and economic-environmental factors. The implementation of this appropriate technology is expected to minimize the risk of heavy metal pollution in a sustainable manner.